2021
DOI: 10.3390/pharmaceutics13060868
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Assisted Distal Pulmonary Distribution of Budesonide Revealed by Mass Spectrometry Imaging

Abstract: Direct lung administration of budesonide in combination with surfactant reduces the incidence of bronchopulmonary dysplasia. Although the therapy is currently undergoing clinical development, the lung distribution of budesonide throughout the premature neonatal lung has not yet been investigated. Here, we applied mass spectrometry imaging (MSI) to investigate the surfactant-assisted distal lung distribution of budesonide. Unlabeled budesonide was either delivered using saline as a vehicle (n = 5) or in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…This is consistent with the findings of Riccardo Zecchi et al In the study, they used mass spectrometry imaging to analyze the distribution of PS/budesonide in lamb lungs, and they demonstrated that compared with the PS/saline group, the PS/budesonide group had a more uniform distribution of budesonide in the lung and more distribution in the peripheral lung. 94…”
Section: The Way Of Administration Of Budesonidementioning
confidence: 99%
“…This is consistent with the findings of Riccardo Zecchi et al In the study, they used mass spectrometry imaging to analyze the distribution of PS/budesonide in lamb lungs, and they demonstrated that compared with the PS/saline group, the PS/budesonide group had a more uniform distribution of budesonide in the lung and more distribution in the peripheral lung. 94…”
Section: The Way Of Administration Of Budesonidementioning
confidence: 99%
“…Budesonide is a potent corticosteroid used in asthma to treat lung inflammation [6]. In its aerosolized form, budesonide remains in the airways; however, when combined with surfactant, it is transported into the more distal lung where BPD occurs [7,8]. Unfortunately in premature infants, budesonide can be detected systemically shortly after intratracheal administration, though it is rapidly metabolized by the liver [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%